Desafios para o consumo sustentável de crédito: a tutela dos (hiper)vulneráveis entre o superendividamento e o cadastro (im)positivo - Silva, Leandro Carvalho dos Santos (2020)
This research aims to analyze the over-indebtedness of the individual consumer and the need for legal protection to combat this phenomenon that is increasingly growing in society. Credit can be considered a economic growth factor for the population, however, its concession without attention to the minimum assumptions for hiring can lead people to financial ruin. The study that is presented sought, therefore, to demonstrate the need for legal protection to consumers with chronic indebtedness, both preventively avoiding the increase of consumers placed in situations of impossibility of defaulting with their obligations, as well as the protection of those who are already in a situation of permanent indebtedness. In this context, we present the relationship between the positive cadastre and the decrease in the asymmetry of information between postulants and credit grantors as a factor to help reduce interest rates and decrease default. Were analyzed bill nº 3.515/2015 and the Positive cadastre Law, Law nº 12.414/2011, with the respective amendments to Complementary Law nº 166/2019, the first with the objective of improving the system of granting credit to the consumer and to have on the prevention and treatment of over-indebtedness; the second seeks to promote changes in the form of cadastre of the consumer in the database, becoming automatic inclusion. Next, we investigate the credit information databases of consumers from other countries, analyzing the outcome of their implementation, as well as the possible effects of their implementation in Brazil. Finally, the effects of the positive cadastre for subjects of the credit relationship are demonstrated, such as their influence on the treatment and prevention of over-indebtedness.